Exploration of Regional Asset Management in the Regional Financial and Asset Agency of Paniai Regency, Central Papua - Damaik, Yudo Tri Kumoro Sapto Nugroho; Abdul. Majid Bakri, Hasniaty Hasniaty , (YUME : Journal of Management, 2024)
The aim of this research is to assess the effectiveness of asset management and provide recommendations for improvement. This research analyzes regional asset management that faces challenges related to infrastructure, resources and information systems. Management is carried out by the Regional Assets Division with a focus on needs planning, control, utilization, inventory and reporting. The research method used is qualitative, collecting data through interviews, observation and document analysis. Research findings show that the existing management system includes policy, planning and evaluation, but is still carried out manually, potentially causing accuracy problems. In addition, inaccurate data and limited personnel training hinder management effectiveness. The application of modern technologies such as asset management software, RFID, and GPS, as well as the development of digital platforms for real-time monitoring, is recommended to increase the efficiency and accountability of regional asset management. Keywords: Regional Asset Management, Effectiveness